Ironies de l'assaig. Ors, Pla, Fuster: història intel·lectual de l'adhesió incompleta - Martí Monterde, Antoni (Caplletra. Revista Internacional de Filologia, 2006)
The main goal of this article is to bring up the topic of irony in the essay as a literary genre, based on the considerations made by Eugeni d’Ors, Josep Pla and Joan Fuster. The emergence of the definition of irony as an incomplete adhesion, which refers to Ors although it has lasted especially through Pla, is revised here; the intellectual history of the definition is analyzed in order to consider in which moment Fuster’s essay relates to it and, taking irony as a starting point, it gives a boost to ontemporary Catalan essay.